Dorsal Root Ganglion Stimulation for Chronic Pelvic Pain: A Case Series and Technical Report on a Novel Lead Configuration. Issue 1 (1st August 2018) - Hunter, Corey W.; Yang, Ajax
Abstract : Introduction: Chronic pelvic pain (CPP) is an elusive and complex neuropathic condition that is notoriously recalcitrant to treatment. The term "CPP" encompasses a number of treatment‐resistant conditions like pudendal neuralgia, interstitial cystitis, coccygodynia, vulvodynia. CPP has been presented neuromodulators attempting to utilize conventional spinal cord stimulation (SCS), with constant frustration and high explant rates. Contrary to SCS, dorsal root ganglion stimulation (DRGS) delivers targeted target to focal areas, does not rely on paresthesias, and is able to reliably capture body parts like the pelvis making it an ideal modality for the treatment of CPP. We present seven patients with intractable CPP, resistant to conventional treatment methods, all successfully treated with DRGS. Methods: The case series includes seven patients with severe, CPP who failed to respond to a variety interventional treatments, and in some cases SCS. All seven patients were successfully trialed with DRGS utilizing leads placed over the bilateral L1 and S2 DRG's—to our knowledge, no publications describing either this particular lead configuration, or utilizing DRG stimulation on CPP, exist. Results: Following treatment, all seven patients experienced significant pain relief as well as reduction in opioid consumption and some cases improvement with sexual function and urination. Four of these patients have been implanted and continue to self‐report sustained pain relief with high‐satisfaction and functional improvement. To date no explants or instances of loss of efficacy have occurred (>1 year since implant). Conclusion: Like most neuropathic pain states, CPP is resilient, difficult to manage, and typically unresponsive to the traditional therapeutics and SCS. Our case series demonstrates no only that DRGS is potentially effective, long‐term treatment modality for CPP, but that the L1/S2 lead placement is the configuration of choice despite distinct differences in etiologies of pain and location.